2006
DOI: 10.1007/s10557-006-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly Purified Omega-3 Fatty Acids for Secondary Prevention of Sudden Cardiac Death After Myocardial Infarction—Aims and Methods of the OMEGA-Study

Abstract: The recruitment-period started in October 2003 and is expected to last until December 2006. The results of the study are therefore expected for the beginning of 2008, when all patients will have completed the 12-months follow up-period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 66 publications
0
21
0
1
Order By: Relevance
“…Burr et al [34] based on a trial of 3114 men with angina, suggested that patients treated with fish oil capsules had a higher risk of sudden cardiac death than untreated control subjects [34]. A Norwegian study by Nilson et al [35] did not show a benefit of ω-3 PUFA supplementation in post-MI patients and in the recently presented OMEGA trial, consisting of 3851 patients with AMI from 104 centers in Germany, EPA/DHA did not show any further benefit on primary or secondary prevention when given together with other specific treatments (e.g., aspirin, clopidogrel, statins, betablockers, and angiotensin-converting enzyme inhibitors) [36].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 96%
“…Burr et al [34] based on a trial of 3114 men with angina, suggested that patients treated with fish oil capsules had a higher risk of sudden cardiac death than untreated control subjects [34]. A Norwegian study by Nilson et al [35] did not show a benefit of ω-3 PUFA supplementation in post-MI patients and in the recently presented OMEGA trial, consisting of 3851 patients with AMI from 104 centers in Germany, EPA/DHA did not show any further benefit on primary or secondary prevention when given together with other specific treatments (e.g., aspirin, clopidogrel, statins, betablockers, and angiotensin-converting enzyme inhibitors) [36].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 96%
“…To establish transparency of design and analysis procedures, study design and methods of the OMEGA trial have previously been described in detail. 18 …”
Section: Definition Of End Points and Monitoringmentioning
confidence: 99%
“…Study size was estimated based on previous registry data with SCD projected to occur in 1.9% in the group treated with omega-3 acid ethyl-esters 90 and 3.5% in the placebo group, and alpha of 2.5% and a power of 80% (Rauch et al, 2006). Primary analysis was by intention-to-treat, and SCD occurred in 1.5% of both verum and placebo groups, with other cardiovascular events also evenly distributed.…”
Section: Intervention Trials With Clinical Endpointsmentioning
confidence: 99%